ZORA 157: Imenitnost slovenskega jezika - Jesenšek, Marko (2024)
ZORA 157: The Eminence of the Slovene Language. Part One of the book The Eminence of the Slovene Language offers my view on the excessive submissiveness of some in the Slovene higher education community to the global capitalist elite, which leads the Slovene higher education in the wrong direction. I am trying to prove how wrong it is for the Slovene language to be displaced by English both in university classrooms and in the scholarly publications of Slovene professors. A reflection on the necessity of Slovene as a language of education or lack of it inevitably brings us to the conclusion that Slovene as a language of education should by no means be robbed of its eminence due to a foreign language (i.e. English). Slovene is the state language of Slovenia. We cannot ignore this fact and it is crucial to understand that Slovene universities cannot function without Slovene. Financial difficulties of the Slovene higher education should not be used as an excuse for recklessly sacrificing Slovene and placing responsibility for the Anglicization of Slovene universities on so-called "internationalization". In Part Two of my book I present the attitudes of my professors and mentors (Martina Orožen, Zinka Zorko, Jože Toporišič, Jožef Smej) with regard to the Slovene language and all that defines respectful scholarly research and responsibiity to the Slovene community writ large.
Keywords: language policy and language planning; Slovene; Article 15 of Higher Education Act on the language of education; Anglicization of Slovene higher education; learning language